2012
DOI: 10.4161/cbt.19294
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 inhibitor NVP-AUY922 enhances radiation sensitivity of tumor cell lines under hypoxia

Abstract: NVP-AUY922, a novel inhibitor of Hsp90, was shown to enhance the effect of ionizing radiation (IR) on tumor cells under normoxic conditions. Since low oxygen tension is a common feature of solid tumors, we explore in the present study the impact of hypoxia on the combined treatment of lung carcinoma A549 and glioblastoma SNB19 cell lines with NVP-AUY922 and IR. Cellular analysis included the colony-forming ability, expression of CAIX, Hsp90, Hsp70, Raf-1, Akt, cell cycle progression and associated proteins, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…For HSP90i and CCRT in bladder cancer, mechanistic studies focused on HER2 and AKT signalling with no investigation of the impact of HSP90i on DDR signalling [ 25 ]. Likewise studies into sensitization to radiation or cisplatin alone often focused on cell cycle, growth and apoptotic signalling pathways [ 22 , 24 , 32 , 34 36 ]. Choi et al identified HSP90i by bioinformatics as a means to convert HR proficient to HR deficient tumours [ 23 ] but DDR analysis was restricted to γH2Ax and RAD51 foci formation as has been the case in other studies [ 17 , 22 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For HSP90i and CCRT in bladder cancer, mechanistic studies focused on HER2 and AKT signalling with no investigation of the impact of HSP90i on DDR signalling [ 25 ]. Likewise studies into sensitization to radiation or cisplatin alone often focused on cell cycle, growth and apoptotic signalling pathways [ 22 , 24 , 32 , 34 36 ]. Choi et al identified HSP90i by bioinformatics as a means to convert HR proficient to HR deficient tumours [ 23 ] but DDR analysis was restricted to γH2Ax and RAD51 foci formation as has been the case in other studies [ 17 , 22 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As Hsp90 inhibitor is known to affect the cell cycle checkpoint [23][24][25][26][27][28][29]32], we also studied cell cycle effects after various combinations of treatment with 17AAG and radiation. Figure 7 shows our cell cycle data.…”
Section: G2 Delay Induced By Carbon Irradiation Is Further Intensifiementioning
confidence: 99%
“…The combination of Hsp90 inhibitor and radiation on tumor cells has been studied and enhancement of radiation effect with the inhibitors has been well documented [18][19][20][21][22][23][24][25][26][27][28][29][30]. Hypoxic tumor cells were also radiosensitized by the combination strategy [31,32]. Some of these studies indicated that, as compared with tumor cells, normal cells might not be affected, indicating a selective radiosensitization of tumor cells [18,19,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recenly, inhibitors of hsp90 with improved bioavailability and lower toxicity have become available, including a series of pyrazole resorcinol compounds that have proven to be stronger inhibitors of hsp90 (NVP-AUY922) 120 . Treatment of cancer cells, including NSCLC, with NVP-AUY922 leads to radiosensitization under normoxic and hypoxic condition 121,122 . The radiosensitization was accompanied by effects on DNA repair, cell cycle progression 123 and abrogation of homologous recombination leading to mitotic entry with unresolved DNA damage 124 .…”
Section: Heat Shock Protein 90mentioning
confidence: 99%